Adopting a Culture of Total Quality Management in Measuring Green Costs and its Reflection in Improving the Indicators of Continuity and Growth a Survey of Some Industrial Companies in Sudan - Faris Abdulzahra Abdulhussin Alkhalidy; Asaad Sasaa Agrab; Hassanein Ali Salman (International Journal of Economics, Management and Accounting, 2024)
Adopting the knowledge of total quality management, which is one of the vital factors in improving the quality of products and services by adopting continuous methodologies for development and improvement when integrating this knowledge with green costs, which focus on measuring the cost of the product while taking into account the environmental impacts, and the importance of the study lies in the fact that the phenomenon of environmental pollution and global warming has become a topic of global interest from the political, economic and financial aspects, and most industrial companies in Sudan do not care enough about measuring green costs. This study aims to provide a scientific theoretical framework by identifying the criteria and rules for determining and measuring green costs and obtaining practical results from the study for the possibility of applying them in Sudanese industrial companies. One of the most important results reached by the study is that adopting the culture of total quality management in measuring green costs improves the indicators of growth and continuity in industrial companies in Sudan.